2018
DOI: 10.14419/ijet.v7i2.29.14298
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped-Blended Model for STEM Education to Improve Students' Performances

Abstract: Flipped-Blended model, a combination of flipped classroom and blended learning environment, has become increasingly popular, especially in K-12 education. Flipped-Blended model takes advantage of technology for a more flexible learning environment and facilitates a more learner-centered as well as a more active learning in classroom. Flipped-Blended can be seen as an innovation and a new learning paradigm. This is more than just flipped the in-class and out-class activities, the flipped-blended also change the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Considering the findings of this research, it suggests to examine the effectiveness of the implementation of STEM integration in chemistry teaching with a deep analysis. The survey could be conducted in the term on how the in-service chemistry teachers integrate STEM using varied pedagogies such as project-based learning [17,36]; problem-based learning [17]; inquiry learning [18] and blended learning [40]. The blended learning became a considerable choice since it could develop students' self-efficacy [41] and students' selfregulated learning [42,43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the findings of this research, it suggests to examine the effectiveness of the implementation of STEM integration in chemistry teaching with a deep analysis. The survey could be conducted in the term on how the in-service chemistry teachers integrate STEM using varied pedagogies such as project-based learning [17,36]; problem-based learning [17]; inquiry learning [18] and blended learning [40]. The blended learning became a considerable choice since it could develop students' self-efficacy [41] and students' selfregulated learning [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…For future studies, it is suggested to use blended learning mode in delivering chemistry content knowledge using STSE approach because the presence of online learning in this mode gives significant effects on students' self-efficacy as the part of motivation expectancy value [44] and students' self-regulated learning [43]. Moreover, the addition of computer assisted instruction could be employ because it enables in improving students' performance and motivation in the certain subject [18] such as through flipped class room [40]. Thus, the effectiveness of collaborative learning based STSE in comprehensive result will be reveal.…”
Section: Resultsmentioning
confidence: 99%
“…Flipped teaching is particularly beneficial in STEM teaching since it provides more in-depth learning of content ( 13 ). The COVID-19 pandemic presented a challenge in the continuation of flipped teaching in its original form due to the necessity of transitioning to online teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The e-learning method has been popular for the past 20 years [1], for not only virtual classes, but also independent courses. The method also allows learning to be conducted in an unlimited space and participants [2,3]. In its development, elearning is commonly combined with a face-to-face interaction [4].…”
Section: Introductionmentioning
confidence: 99%